A Tale of two museums in the 1930s: Ethnographic Politics in Paris and Hanoi - Dias, N. (The Picturesque Eye, 2015)
The Musée de l’Homme (Hanoi) was envisaged as a replica of the Musée de l’Homme (Paris), a sign of the mutual mirroring characterizing the relationships between metropolis and colony. At the same time, something more than mutual mirroring was involved in the relations between metropolis and colony. The presentation explores the relations between the exhibition practices of these two institutions and the ways in which the displays at both museums contributed to the production and circulation of particular conceptions of Indochinese culture through which governmental action was brought to bear on the task of managing the relations between colonizers and colonized.